2018
DOI: 10.1016/j.ejca.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Management and 5-year outcomes in 9938 women with screen-detected ductal carcinoma in situ: the UK Sloane Project

Abstract: Recurrent DCIS or invasive cancer is uncommon after screen-detected DCIS. Both RT and endocrine therapy were associated with a reduction in further events but not with breast cancer mortality within 5 years of diagnosis. Further research to identify biomarkers of recurrence risk, particularly as invasive disease, is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 30 publications
3
52
1
Order By: Relevance
“…Since mortality does not seem to be substantial after a diagnosis of DCIS, the primary concern is defining the risk that untreated DCIS progresses to invasive disease or that surgically treated DCIS recurs as DCIS or as invasive cancer, as an invasive recurrence may affect survival. Looking into type of breast surgery offered, breast conservation becomes more common with older age, reaching a plateau after 60 y, according to a report from the Sloane Project [52]. Two studies from the USA [37,38] also showed that this trend is larger for women N70y, implying that older age does not only affect whether surgery will be offered, but also type of surgery, with a trend to avoid mastectomy.…”
Section: Surgical Treatment and Outcomesmentioning
confidence: 99%
“…Since mortality does not seem to be substantial after a diagnosis of DCIS, the primary concern is defining the risk that untreated DCIS progresses to invasive disease or that surgically treated DCIS recurs as DCIS or as invasive cancer, as an invasive recurrence may affect survival. Looking into type of breast surgery offered, breast conservation becomes more common with older age, reaching a plateau after 60 y, according to a report from the Sloane Project [52]. Two studies from the USA [37,38] also showed that this trend is larger for women N70y, implying that older age does not only affect whether surgery will be offered, but also type of surgery, with a trend to avoid mastectomy.…”
Section: Surgical Treatment and Outcomesmentioning
confidence: 99%
“…Moreover, only a minority of DCIS patients will benefit from these findings, since only 9-12% of DCIS are low grade. 13,24,[40][41][42] Additional inclusion criteria besides nuclear grade will further decrease the number of eligible patients. The overall impact of active surveillance trials on the population of DCIS patients might therefore be limited.…”
Section: Is Active Surveillance a Noninferior Alternative?mentioning
confidence: 99%
“…Patient recruitment might be facilitated by including patients of previously conducted randomized clinical trials and retrospective studies, of which a nonexhaustive selection is summarized in Table 2. 17,19,20,24,41,70,[90][91][92][93][94][95][96][97] Inclusion of these patients in a study conducted according to the new research strategy would allow for correction of treatment effects, since a substantial number of patients are treated with radiotherapy and/or TAM after BCS. Additionally, it would be interesting to also include HER2-positive DCIS patients with recurrences from the currently ongoing NSABP B-43 trial, wherein the value of adjuvant trastuzumab is investigated.…”
Section: Practical Implementation Of the Alternative Research Strategymentioning
confidence: 99%
See 2 more Smart Citations